(untitled) (EAAE Annual Conference Proceedings, 2025)
The practice of architecture stands at the threshold of a major paradigm shift. The longstanding model – rooted in Enlightenment ideals that equated development and progress with new construction – is increasingly being questioned. In its place, alternative practices are emerging that promote new sensibilities, attitudes, and mindsets. As Enlightenment ideals give way to new materialist perspectives, a once-marginalized vocabulary – centered on care, repair, and empathy – is regaining prominence in architectural discourse. Restoration, once primarily associated with historical and cultural monuments, is now being reconsidered in relation to all existing structures. This shift reflects a growing sense of necessity and ethical responsibility on the part of architects toward the planet, cities, and communities. The architectural profession is moving away from the image of the white, European, male architect – portrayed as a prophetic figure – toward a more grounded vision of the architect as a specialized and responsible citizen. This alternative paradigm calls for a redefinition of architectural education as well. The culture of architecture schools must be critically re-examined, making space for concepts such as care and repair within curricula. This re-evaluation should encompass the types of courses offered, the nature of design studio projects, and the pedagogical approaches employed. Furthermore, the imperative to care for the planet must be extended to caring for students themselves, beginning with a reconsideration of the jury system. This paper explores how integrating practices of care can contribute to repairing the institutional and pedagogical structures of architecture schools.